Advances in Complex Valvular Disease (IntechOpen, 2021)
As the diagnostic and therapeutic tools for the management of complex cardiac valve disease continue to evolve, the options for patients who previously had few choices continue to expand. Such advances have resulted in a renaissance in how Heart Teams approach problems and have been able to engage patients in shared decision-making conversations towards a common goal. While opportunities exist in the management of physiologically challenging congenital heart disease, the vast explosion of research and development in the area of aortic valve disease has offered new hope to patients for improving their quality and quantity of life. The goal of this text is to hopefully serve as a foundation for those who want to explore such topics in greater detail.